Determination of Resistance to Water-İnduced Damage of Bituminous Mixtures Containing Hydrated Lime Prepared with Different Contents of PVC Waste - Görkem, İsmail Çağrı; Artagan, Salih Serkan; Kayaalp, Bekir Tuna; Saykan, Cem; Özdemir, İmer Arda (Fırat University, 2024)
Increasing commercial mobility throughout the world has increased the need for roads and as a result, new road networks have emerged. The pavement type of the highways constructed in our country consists of flexible pavements to a significant extent. Parameters such as the number of heavy vehicles, repeated loads as well as environmental and climatic conditions cause different deformations on flexible pavements. One of these deformations is water-induced damage. In particular, changing climatic conditions cause some regions to experience intense precipitation in a very short period of time, which they should receive throughout the year. As a result, flexible pavements are damaged and their service life becomes shorter than expected. With increasing environmental awareness, the use of some waste materials in bituminous mixtures has become an extremely important issue. In this study, bituminous materials modified with different Polyvinyl Chloride (PVC) contents were mixed with properly graded aggregates and their resistance to water-induced damage has been evaluated. In addition, several performance tests were carried out to evaluate the effect of hydrated lime addition on the resistance of the samples to water-induced damage. In this context, the properties of the modified bitumen and aggregates were determined by performing conventional bitumen and aggregate tests. As the final objective of the study, Modified Lottman Test (AASHTO T 283) was performed on the mixtures to determine the effect of PVC addition to bituminous materials on resistance to water-induced damage.

Dünya genelinde artan ticari hareketlilik yollara olan ihtiyacı artırmış ve bunun sonucunda yeni yol ağları ortaya çıkmıştır. Ülkemizde inşa edilen karayollarının üstyapı tipi önemli ölçüde esnek kaplamalardan oluşmaktadır. Ağır taşıt sayısı, tekrarlanan yükler, çevre ve iklim koşulları gibi parametreler esnek kaplamalar üzerinde farklı deformasyonlara neden olmaktadır. Bu deformasyonlardan biri de su kaynaklı hasarlardır. Özellikle değişen iklim koşulları bazı bölgelerin yıl boyunca alması gereken yağışları çok kısa sürelerde yoğun olarak almasına neden olmaktadır. Bunun sonucunda esnek kaplamalar hasar görmekte ve hizmet ömürleri beklenenden daha kısa olmaktadır. Artan çevre bilinciyle birlikte, bazı atık malzemelerin bitümlü karışımlarda kullanılması son derece önemli bir konu haline gelmiştir. Bu çalışmada, farklı Polivinil Klorür (PVC) içerikleri ile modifiye edilmiş bitümlü malzemeler uygun gradasyonlu agregalar ile karıştırılmış ve su kaynaklı hasarlara karşı dirençleri değerlendirilmiştir. Ayrıca, sönmüş kireç ilavesinin numunelerin su kaynaklı hasara karşı direnci üzerindeki etkisini değerlendirmek için çeşitli performans testleri gerçekleştirilmiştir. Bu kapsamda, modifiye edilmiş bitüm ve agregaların özellikleri, geleneksel bitüm ve agrega testleri yapılarak belirlenmiştir. Çalışmanın son hedefi olarak, bitümlü malzemelere PVC ilavesinin su kaynaklı hasara karşı dirence etkisini belirlemek amacıyla karışımlara Modifiye Lottman (AASHTO T 283) Deneyi uygulanmıştır.
Farklı İçeriklerde PVC Atığı ile Hazırlanan Sönmüş Kireç İçeren Bitümlü Karışımların Suya Bağlı Bozulmalara Karşı Direncinin Belirlenmesi
Keywords: Transportation Engineering; Ulaştırma Mühendisliği